2009
DOI: 10.2527/jas.2008-1452
|View full text |Cite
|
Sign up to set email alerts
|

Ideal amino acid balance for sows during gestation and lactation1

Abstract: Improving efficiency of protein utilization is important for pregnant sows under restricted feed allowance and for lactating sows with limited feed intake. Sows have limited ability to support the growth of fetuses and mammary glands during late gestation and to support mammary growth and milk production, especially during first lactation period. A series of studies was conducted to characterize requirements and ideal ratios of AA for 1) fetal growth, 2) mammary gland growth of gestating sows, 3) maternal tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
115
0
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(129 citation statements)
references
References 53 publications
7
115
0
7
Order By: Relevance
“…This study utilized multiparous sow to better comprehend the status of oxidative stress during different stages of reproduction. The performance of all sows in this study was normal, which is similar to our previous publications, with regard to BW gain during gestation, BW changes during lactation, feed intake during gestation and lactation, litter size, litter birth weight and litter weight gain (Mateo et al, 2007(Mateo et al, , 2008(Mateo et al, and 2009Kim et al, 2009). In this study, there was no truly non-pregnant sow to compare the oxidative damage with pregnant sow because of practical difficulty in obtaining non-pregnant sows with similar age, parity and BW to those used in this study.…”
Section: Discussionsupporting
confidence: 89%
“…This study utilized multiparous sow to better comprehend the status of oxidative stress during different stages of reproduction. The performance of all sows in this study was normal, which is similar to our previous publications, with regard to BW gain during gestation, BW changes during lactation, feed intake during gestation and lactation, litter size, litter birth weight and litter weight gain (Mateo et al, 2007(Mateo et al, , 2008(Mateo et al, and 2009Kim et al, 2009). In this study, there was no truly non-pregnant sow to compare the oxidative damage with pregnant sow because of practical difficulty in obtaining non-pregnant sows with similar age, parity and BW to those used in this study.…”
Section: Discussionsupporting
confidence: 89%
“…Similarly, there is lack of knowledge on whether efficiencies change during lactation depending on feed intake or when sows turn from the anabolic to catabolic state. Kim et al (2009) found that the order and ratios of the first limiting AA changed depending on the BW loss of the sow, which also emphasizes the complexity of AA nutrition in lactating sows and the need of generating more knowledge in this area.…”
Section: Resultsmentioning
confidence: 89%
“…Specific feed formulations could be made for different groups of sows -for example, first parity sows may have a different requirement than multiparous sows. Sows could also be divided into groups according to their body size or body condition, as Kim et al (2009) suggest that the AA requirement during lactation might depend on the body condition of the sow.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of production systems do not have formal strategies to feed sows differentially based on their own and gestating litter requirements, although adapting feeding level according to sow body condition may indirectly go some way towards achieving this goal. Not adapting gestational feeding to individual requirements can place both sows and piglets (Kim et al, 2009) in a sub-optimal state before farrowing and increase the necessity of obtaining high lactation intakes to meet energy requirements. This is not always possible, as seasonal constraints such as high temperature, parity effects (Hermesch and Jones, 2007) and health issues ) can hinder lactation intake.…”
Section: Discussionmentioning
confidence: 99%